Profitability Analysis of Indonesian Pharmaceutical Manufacturing Companies: Capital Structure and Company Size - Sri Dwiningsih; Anwar Sanusi; Edi Subiyantoro (Trescode Green Organization, 2024)
The aim of the author in conducting this research is to determine the influence of capital structure and company size on the profitability of pharmaceutical companies listed on the Indonesia Stock Exchange. The method used by the author in conducting this research is descriptive analysis method and multiple linear regression analysis. Data processing was carried out using IBM SPSS STATISIC 25. The population of this study was all pharmaceutical companies listed on the Indonesia Stock Exchange in 2020-2022 with the number of samples taken according to the researchers' criteria of 10 pharmaceutical companies. The partial research results show that the Capital Structure (DAR) variable has a negative and significant effect on Profitability (ROE) in pharmaceutical companies, the Company Size (FS) variable has no significant effect on Profitability (ROE) in pharmaceutical companies, simultaneously the Capital Structure (DAR) variable, and Company Size (FS) has a significant effect on Profitability (ROE) in pharmaceutical companies.